The Determination of Ensiled Qualities of Corn, Alfalfa and Sugar Beet Pulp and the Effects on Food Intake and Nutrient Digestibility When Fed to Lambs in Different Forms - Tatli, Pinar; Çerçi, I. Halil; Gürdo?an, Fuat (My University, 2001)
This study was conducted in two stages to determine the ensiled qualities of corn, alfalfa and sugar beet pulp, and the effects on food intake and nutrient digestibility of corn and alfalfa silages used alone, together and with sugar beet pulp silage in lambs. In the first stage, corn, alfalfa and sugar beet pulp were ensiled and silos were opened after 45 days. Silage samples were taken for determination of silage quality and the samples were analysed. Dry matter (DM) levels of corn, alfalfa and sugar beet pulp silages were found to be 28.56 and 31.44, 16.74%, respectively. The pH, NH3-N and lactic acid levels of silages were found to be 4.00, 4.92, 4.15; 0.31, 0.76 and 0.40 % (DM); and 3.10, 1.78 and 2.14 % (DM) respectively. In the second stage, four male Akkaraman lambs 9 months of age weighing an average of 33 kg were used. The experiment was carried out with individual boxes of 4X4 Latin square design. Corn, alfalfa and sugar beet pulp were used as silage materials. This study included four groups. Group I had 100% corn silage; group I had 100% alfalfa silage; group III had 50% corn silage alfalfa silag; group IV had 25% corn silage +25 % alfalfa silage +50 % sugar beet pulp silage. Dry matter intakes of lambs were found to be 1032.87, 551.98, 872.7 and 833.49 g in groups I, II, II and IV respectively (P<0.05). Dry matter, crude protein and cellulose digestibility were found to be 71.82, 62.80, 67.35 and 63.50%; 65.53, 71.93, 70.69 and 57.68%; and 72.93, 67.73, 71.60 and 71.82% in the groups, respectively (P<0.01).
Misir, Yonca ve Yaş Şeker Pancari Posasinin Silolanma Niteliklerinin Belirlenmesi ile Bu Silajlarin Farkli Formasyonlarda Koyunlara Verilmesinin Yem Tüketimi ve Sindirilebilirlik Üzerine Etkisi
Keywords: Alfalfa; Corn; Lamb; Silage; Sugar Beet Pulp